2011
DOI: 10.1007/s11065-011-9165-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional Neuroimaging in the Examination of Effects of Prenatal Alcohol Exposure

Abstract: Functional neuroimaging offers the opportunity to understand the effect of prenatal alcohol exposure on the activities of the brain as well as providing a window into the relationship between neural activation and the behavioral outcomes that have been described in affected individuals. Several different methodologies have been used to examine the neurophysiological signal changes associated with different brain functions in prenatally exposed individuals and those diagnosed with fetal alcohol syndrome (FAS) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 64 publications
(91 reference statements)
2
43
0
Order By: Relevance
“…13,98 Reduction of the overall brain size has been the most consistent finding in children with FASD. 13 Several macrostructural abnormalities, like malformations of the corpus callosum and cerebellar atrophy, have been reported in prenatally alcohol-exposed children.…”
Section: Mri Studies Of Prenatally Drug-exposed Childrenmentioning
confidence: 97%
“…13,98 Reduction of the overall brain size has been the most consistent finding in children with FASD. 13 Several macrostructural abnormalities, like malformations of the corpus callosum and cerebellar atrophy, have been reported in prenatally alcohol-exposed children.…”
Section: Mri Studies Of Prenatally Drug-exposed Childrenmentioning
confidence: 97%
“…While this approach is purportedly less subject to confounding than traditional epidemiological methods, the validity of these inferences still depends on the reliability and validity of self-reported alcohol consumption during pregnancy. Neuroimaging studies have explored the effects of alcohol on neurodevelopment [6,9]. These studies often compare in utero alcohol-exposed persons with 'normal' controls who have had no or low in utero alcohol exposure [9].…”
Section: Current Understandings Of Fasdmentioning
confidence: 99%
“…Neuroimaging studies have explored the effects of alcohol on neurodevelopment [6,9]. These studies often compare in utero alcohol-exposed persons with 'normal' controls who have had no or low in utero alcohol exposure [9]. However, there are a number of issues that may affect the validity of these studies: 1) the way in which 'normal' and 'exposed' cases are identified may be subject to a number of systematic biases; 2) studies to date have not followed up subjects over time and, therefore, it is unclear whether observed differences between cases and controls persist, or tend to the population norm, over time; 3) neuroimaging studies can only identify brain differences associated with cognitive deficits between cases and controls; they cannot determine whether prenatal alcohol exposure is the cause of the difference; and finally 4) prenatal alcohol exposure can produce microcephaly, where a significantly smaller brain develops compared with that of non-alcohol exposed individuals.…”
Section: Current Understandings Of Fasdmentioning
confidence: 99%
See 2 more Smart Citations